Analisis Kemampuan Berbicara Mahasiswa Melalui Media Youtube - Sulaiman Ahmad (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
The ability to speak students through YouTube is important to consider certain aspects that affect the quality of communication. Analysis of students' speaking skills through YouTube media can also be a foundation for developing more effective learning strategies in academic environments. The research method used in this study is qualitative research method. The source of data in this study is 24 videos uploaded via youtube by students as a follow-up to the assignment of warament courses. With the results obtained that YouTube media is enough to contribute to warament courses for students. Although for students who are not used to speaking in front of the camera, they are quite difficult in pronouncing a sentence, but in the end they become motivated by preparing mentally, the text contains information that will be conveyed in the video.